Tragedi Monumen Nasional Merupakan Cambuk Bagi Negara Kesatuan Republik Indonesia: (Studi Kasus Sosial Kemasyarakatan) - Yosef Moan Banda (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
Realizing that the State Unitary Republic of Indonesia (NKRI), today raised many social ills. And one of them marked by unrest Monas tragedy on June 1, 2008. Many of the cases or conflict occur in Indonesia, linked human rights, freedom of association. Freedom of religion and belief, each as stipulated in the 1945 Constitution Chapter X a from chapter statisfied with distribution of “cake of power”. This research is conducted in the from of a literature review that explore issues of social in llife. The method used to analyze news related to actual conflict published in the electronic media, as well as print media. Goals of this study is conflict and violence conflict is called open conflict, the conflict is rooted in and very real. As a democratic country acts Islamic Defenders Front (FPI) is not justified by the acts forced to play, and the more depressing that attacks on those groups that do not like, including the women and children who are innconcent. Trauma and pain experienced in the past, governments often underestimated as experience personal and collective experience about pain, loss, pain, and violence; This is often an obstacle in dealing with conflicts.